Working Group Report on I S M and Homoeopathy for the Eighth Five Year Plan - Planning Commission (Planning Commission, 1989)
Indian Systems of Medicine includes Ayurveda, Siddhi and Unani Systems of Medicine and also Yoga and Naturopathy there Dec. These systems hove a long heritage in this country., The practitioners of these systems are often part of the local community culture and traditions and continue to have high social standing almost in every part of the country. The practitioners of these systems are exerting considerable influence and respect among the people specially living in rural end remote areas. The Homoeopathy system of medicine was introduced in this country during the early 19th century and thereafter spread almost in every state. Based on scientific and rational principles, these systems stood the test of time and proved their efficacy over the generations.
Government of India Planning Commission
Government of India Planning Commission